1986
DOI: 10.1007/bf02013458
|View full text |Cite
|
Sign up to set email alerts
|

Gangrenous cholecystitis and acute cholangitis associated with anaerobic bacteria in bile

Abstract: The incidence of anaerobic bacteria in bile, and the relationship between bacterial species isolated from the bile and the clinical characteristics of disease in these patients was studied. One hundred and twenty-five bile specimens obtained during surgery from the same number of patients were cultured aerobically and anaerobically. Seventy patients (56%) had positive cultures and in 30% of the patients with positive cultures anaerobic bacteria were recovered, usually together with aerobic bacteria. Members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
2
19
0
1
Order By: Relevance
“…These findings indicated that Enterobacteriaceae might be the primary causative organisms of AC. In agreement with our findings, other studies have implicated several genera of Enterobacteriaceae, including E. coli, Klebsiella pneumonia, Salmonella, to be the main pathogenic bacteria in bile flora[8, 43,44].A strong correlation between the quantities of Enterobacteriaceae existing in the gut and bile flora was also found. According to the data fromAlmeida et al, E. coli infection can degrade intestinal barrier and thereby compromise its integrity[45].…”
supporting
confidence: 91%
“…These findings indicated that Enterobacteriaceae might be the primary causative organisms of AC. In agreement with our findings, other studies have implicated several genera of Enterobacteriaceae, including E. coli, Klebsiella pneumonia, Salmonella, to be the main pathogenic bacteria in bile flora[8, 43,44].A strong correlation between the quantities of Enterobacteriaceae existing in the gut and bile flora was also found. According to the data fromAlmeida et al, E. coli infection can degrade intestinal barrier and thereby compromise its integrity[45].…”
supporting
confidence: 91%
“…Biliary penetration of antibiotic agents should be considered as well, but is less important than efficacy against suspected bacteria. The clinical context also must be appreciated, because it has been shown that anaerobic bacteria are found more frequently in severe cholangitis than in mild cases [28][29][30]. Similarly, hospital-acquired cholangitis is often caused by multiple and/or resistant organisms, such as Pseudomonas spp, methicillin-resistant Staphylococcus aureus, and vancomycin-resistant enterococci, whereas the infection in community-acquired cases is mostly caused by a single species of intestinal microorganism, such as E. coli, Klebsiella, and Enterococcus spp.…”
Section: Therapeutic Managementmentioning
confidence: 99%
“…Since the empirical antibiotic is only a bridge to the proper treatment, which is based on the culture results, it is important to select an effective empirical antibiotic. Many cholangitis patients with positive blood cultures have been found to have the same bacteria in their blood as those isolated from the bile cultures [41,42]. Therefore, microbial information gathered from bile cultures should provide valuable therapeutic guidance.…”
Section: Discussionmentioning
confidence: 99%